SURGICAL THERAPHY FOR PRIMARY GLAUCOMA IN DR. KARIADI GENERAL HOSPITAL SEMARANG DURING JANUARY 2020 TO DECEMBER 2022: Oral Presentation - Observational Study - Resident - Maharani; Bestari, Zeta Aisyah; Puspasari, Denti L.; Rahmi, Fifin L. (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma can be treated with medicamentose, non invasive surgery, and invasive surgery. Thisstudy aim to determine the frequency and type of invasive surgery for primary glaucoma in Dr.Kariadi General Hospital during January 2020 to December 2022. MethodsThis was a descriptive research using secondary data obtained from electronic medical records,consist of gender, age, diagnosis, and type of surgery. The sample were taken with purposivesampling which are fullfill the inclusion criteria. ResultsThere were total of 395 eyes (395 patients) with primary glaucoma who underwent surgery, consistof 33% patients with open angle glaucoma (POAG) and 67% patients with angle closure glaucoma(PACG). Most common surgical theraphy for POAG was trabeculectomy (37%), followed bycombination of trabeculectomy and cataract surgery (32%), cataract surgery (16%),cyclocryotheraphy (10%), implantation of glaucoma drainage device (4%), and goniosynechialysis(1%). For PACG, most often used was combination of trabeculectomy and cataract surgery (61%),cataract surgery (13%), cyclocryotheraphy (12%), trabeculectomy (11%), combination of cataractsurgery and goniosynechialysis (2%), and implantation of glaucoma drainage device (1%). ConclusionThe most common type of surgery was trabeculectomy for primary open angle glaucoma andcombination of trabeculectomy and cataract surgery for primary angle closure glaucoma.